2013
DOI: 10.1177/1740774513494503
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact and costs of three strategies used to recruit acutely unwell young children to a randomised controlled trial in primary care

Abstract: Trial recruiter expertise and deployment of several interdependent, illness-specific strategies were key factors in achieving rapid recruitment of young children to a community-based randomised controlled trial (RCT). The 'remote' recruitment strategy was shown to be more cost-effective compared to 'community' and 'local' strategies in the context of this trial. Future trialists should report recruitment costs to facilitate a transparent evaluation of recruitment strategy cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The total cost of recruitment for THRIVE was £182,975, reflecting approximately 13% of the total study budget, and equating to £377 to recruit each randomised participant. These costs are within the range reported by other studies that employed similar recruitment strategies with a combination of practitioner-led, researcher-led and self-referrals [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The total cost of recruitment for THRIVE was £182,975, reflecting approximately 13% of the total study budget, and equating to £377 to recruit each randomised participant. These costs are within the range reported by other studies that employed similar recruitment strategies with a combination of practitioner-led, researcher-led and self-referrals [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 74%
“…Spending time with participants and being able to discuss the study in detail also helped build trust between the research nurses and potential participants, which was cultivated throughout the study by continuity between recruitment, baseline and follow-up appointments, where possible. Other studies using a similar approach, with study-specific research staff to support recruitment have also demonstrated the benefits of this [ 24 , 29 ].…”
Section: Discussionmentioning
confidence: 98%